56.8k views
3 votes
Which expression represents a quadratic expression in complete factored form?

A. (x+4)(x-3)
B. (x-1)(3x-9)
C. (2x+4)(x+3)
D. (x-2) + (x+3)


ANSWER PLSSSSSSSSSSSSS, thanks.

2 Answers

2 votes

Answer:

Have a great rest of your day :)

Explanation:

Which expression represents a quadratic expression in complete factored form? A. (x-example-1
User Aron Rotteveel
by
6.1k points
3 votes

Answer:

A. (x+4)(x-3)

Explanation:

x+4=0 or x-3=0

x=-4 or x=3

User Kathara
by
5.8k points